Investigating Dynamic Molecular Events in Melanoma Cell Nucleus During Photodynamic Therapy by SERS - Yue, Jing; Liang, Lijia; Shen, Yanting; Guan, Xin; Zhang, Jing; Li, Zhiyuan; Deng, Rong; Xu, Shuping; Liang, Chongyang; Shi, Wei; Xu, Weiqing (Frontiers in Chemistry, 2019)
Photodynamic therapy (PDT) involves the uptake of photosensitizers by cancer cells and the irradiation of a light with a specific wavelength to trigger a serious of photochemical reactions based on the generation of reactive oxygen, leading to cancer cell death. PDT has been widely used in various fields of biomedicine. However, the molecular events of cancer cell nucleus during the PDT process are still unclear. In this work, a nuclear-targeted gold nanorod Raman nanoprobe combined with surface-enhanced Raman scattering spectroscopy (SERS) was exploited to investigate the dynamic intranuclear molecular changes of B16 cells (a murine melanoma cell line) treated with a photosensitizer (Chlorin e6) and the specific light (650 nm). The SERS spectra of cell nucleus during the PDT treatment were in situ recorded and the spectroscopic analysis of the dynamics of nucleus uncovered two main events in the therapeutic process: the protein degradation and the DNA fragmentation. We expect that these findings are of vital significance in having a better understanding in the PDT mechanism acting on cancer cell nucleus and can further help us to design and develop more effective therapeutic platforms and methods.